Entanglement generation through particle detection in systems of identical fermions - Bouvrie Morales, Peter Alexander; Valdés-Hernández, Andrea; Majtey, Ana Paula; Zander, Claudia; Plastino, Ángel Ricardo (2024)
Artículo finalmente publicado en: Bouvrie Morales, P. A., Valdés-Hernández, A., Majtey, A. P., Zander, C. y Plastino, A. R. (2017). Entanglement generation through particle detection in systems of identical fermions. Annals of Physics, 383, 401-415. https://doi.org/10.1016/j.aop.2017.06.004